Peripheral muscle dysfunction in idiopathic pulmonary arterial hypertension. Issue 2 (30th August 2009) - Mainguy, Vincent; Maltais, François; Saey, Didier; Gagnon, Philippe; Martel, Simon; Simon, Mathieu; Provencher, Steeve
Abstract : Background: A majority of patients with idiopathic pulmonary arterial hypertension (IPAH) display persistent exercise intolerance despite new specific therapies. Whether patients with IPAH exhibit peripheral muscle dysfunction that may contribute to this limitation remains unknown. The hypothesis that the muscles of patients with IPAH are weaker and display morphological changes compared with those of control subjects and that those changes partly correlate with their exercise capacity was tested. Objective: To characterise quadriceps function, morphology and the enzymatic profile of patients with IPAH. Methods: Exercise capacity, limb muscle cross-sectional area by CT scan, quadriceps strength by maximal voluntary contraction and non-volitional magnetic stimulation of the femoral nerve (quadriceps twitch; TWq), and muscle morphology and enzymatic profile by quadriceps biopsy of 10 patients with IPAH were compared with those of 10 matched controls subjects. Results: Patients with IPAH displayed a lower proportion of type I muscle fibres (p=0.05), a lower maximal voluntary contraction (p=0.05) and TWq (p=0.01), and an increased muscular phosphofructokinase/3-hydroxyacyl-CoA-dehydrogenase ratio (p=0.05). They also tended to have lower thigh muscle cross-sectional area (p=0.15). Maximal oxygen uptake correlated with quadriceps strength (R 2 =0.42, p=0.04), and oxygen uptake at anaerobic threshold correlated with muscle oxidative capacity assessed by oxidative enzyme level for citrate synthase (R 2 =0.45, p=0.05) and 3-hydroxyacyl-CoA-dehydrogenase (R 2 =0.86, p<0.01), and type I fibre capillarity (R 2 =0.57, p=0.02). Conclusion: Patients with IPAH present significant peripheral muscle changes that partly correlated with their exercise capacity.